Gut microbiota causally affects drug-induced liver injury via plasma metabolites: a Mendelian randomization study - Fu, Haoshuang; Zhao, Shuang; Song, Shuying; Xie, Qing (Frontiers in Microbiology, 2024)
The gut microbiota and plasma metabolites have important roles in the progression of drug-induced liver injury (DILI). We investigated the causal associations between gut microbiota, plasma metabolome and DILI.The summary data of gut microbiota (n=18,340), plasma metabolome (n=8,299), and DILI (n=366,838) were obtained from the large genome-wide association studies. Two-sample Mendelian Randomization was performed to explore the associations between gut microbiota, plasma metabolome and DILI. Two-step Mendelian Randomization was performed to explore the potential metabolites.Five taxa were causally associated with DILI, including Oscillospira (OR=2.257, 95%CI=1.110-4.590), Blautia (OR=2.311, 95%CI=1.010-5.288), Roseburia (OR=2.869, 95%CI=1.429-5.761), Fusicatenibacter (OR=1.995, 95%CI=1.024-3.890), and Prevotella7 (OR=1.1549, 95%CI=1.065-2.253). Moreover, fifty-three metabolites were causally associated with DILI. After mediation analysis, four taxa affected DILI via five mediation metabolites. N6-carbamoylthreonyladenosine mediated the effect of Blautia on DILI. Acetylcarnitine mediated the effect of Fusicatenibacter on DILI. And 4-cholesten-3-one mediated the effect of Prevotella7 on DILI. Furthermore, 5,6dihydrothymine levels and salicylate to citrate ratio mediated the effect of Oscillospira on DILI, respectively.We revealed that gut microbiota could affect DILI via plasma metabolites, which could serve as potential biomarkers for risk stratification and underlying mechanism for further investigation of DILI.